Hiroki Yokota, Capacités dynamiques et diversité des modèles de firmes japonaises : une étude de cas et une illustration à partir de l’analyse historique de l’industrie automobile - Hiroki Yokota (Revue de la Régulation)
The purpose is to study the diversity of Japanese firm models from a long-term perspective in order to revisit the concept of the representative model. From the historical analysis of Japanese firms, our thesis emphasizes that the diversity of firms, which clearly emerged during the lost decades, results from their different trajectories and mechanisms of firm growth. The comparative case studies of dynamic innovating capabilities in the Japanese car industry, namely in Toyota and Honda, shows that the diversity of firm models is not an exception. On the contrary, this diversity exists in the long run and has been evolving in the same national and sectorial environment for a long time.